Juego como técnica de aprendizaje y su incidencia en el proceso de enseñanza y aprendizaje en los niños de educación inicial de la Escuela Montevideo del cantón Buena Fé, del año 2021 - Alvarado Estrada, Violeta Margoth (2021)
In the process of research carried out at the Montevideo educational tax institution in the Canton Good Faith, the study and analysis was carried out through the collection of information in person, through a field study applying the participating observation and field journal for data collection, of the main teaching strategies applied to the Teaching and Learning Process in a group of students of Initial Education , supported by the generation of game-focused pedagogical strategies to establish the impact they have as means of support for achieving meaningful learning. Recognizing further that the game is a fundamental part of children's lives, it has proceeded to investigate the essential characteristics of the game and its application to initial education and the discovery of the multiple physical, psychic and social skills it develops in the infant. It has been possible to recognize through this research the role that the game plays in the development of independence and autonomy, since by playing the child learns to take initiatives, to socialize and to work cooperatively with others This research was carried out through a qualitative approach, with the development of a type of documentary or bibliographic research, addressed under the scientific question What is the role of the game as a teaching technique and how does it contribute to the development of the Learning Teaching Process in initial education? As main results, it was possible to assimilate that the game is one of the most useful educational tools to teach the child in a meaningful way, and that it is necessary that in the initial education centers playful processes are carried out as methodological resources that contribute to the integral development and training of the child as a human being and in turn, the game was understood as an educational tool that the teacher should use in his educational practices.